EFEKTIVITAS METODE QUANTUM LEARNING DALAM PEMBELAJARAN BAHASA ARAB KELAS VII DI MTS NAJAHIYAH PALEMBANG - zuhaida, yuniar primarani; haris, M. Harits Akbar; Mukmin; Rendi Sabana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The purpose of this study is to identify the effectiveness of using the Quantum Learning approach to classroom Arabic instruction VII MTs Najahiyyah Palembang. A single group pretest-posttest strategy was employed in this study using research subjects consisting of 20 class VII A students. The research was conducted over five meetings during the odd semester of the 2024/2025 academic year, beginning with 25 September to 9 October 2024. . The study's findings demonstrated that there was a noteworthy rise in pretest and posttest scores after implementing the Quantum Learning method. Based on data analysis, the average student pretest score was 46, while the average posttest score reached 88.5, with a difference of 42.5 points. The N-Gain test shows an increase proportion of 77.8%, falling within the category of effective. Hypothesis testing using the Wilcoxon Signed Rank Test Using the Wilcoxon Signed Rank Test to test hypotheses shows the calculated W value of 210 which is greater than W table 52, so that Ho is turned down while Ha is approved, indicating that the use of The Quantum Learning approach works well for raising students' Arabic language skills. This research concludes that the utilization of the Quantum Learning method can significantly increase Arabic language learning outcomes.